Distribution of Gingival Inflammation in Mouth Breathing Patients: An Observational Pilot Study - Sharma, Rajinder Kumar; Bhatia, Anu; Tewari, Shikha; Narula, Satish Chandar (Journal of Dentistry Indonesia, 2016)
Background: Mouth breathing has been reported to affect gingival health in children. However, studies on the effect of mouth breathing in adult patients are scarce. The objective of present cross sectional study was to examine the relationship between mouth breathing and gingival condition and to evaluate the distribution of gingival inflammation in young adult mouth breathing patients. Methods: Study groups comprised of participants with mouth breathing (test group) and nose breathing (control group) patients with gingivitis. Both the groups underwent periodontal examination. PI, GI and BOP % sites were recorded and analyzed statistically for the differences in mean values. Results: Mouth breathing patients showed higher full mouth GI and BOP scores. Upper anterior segment in mouth breathing patients showed highest GI and BOP followed by lower anterior segment, lower posterior and upper posterior region. Conclusion: Within the limits of present study, our findings suggest that relative to control group participants, test group i.e. patients with mouth breathing had higher gingival inflammation and bleeding sites in upper anterior region.